A Rare Case of Subarachnoid Hemorrhage caused by Ruptured Venous Varix Due to Dural Arteriovenous Fistula at the Foramen Magnum Fed Solely by the Ascending Pharyngeal Artery - Kim, Hyunjun; Lee, Yoon-Soo; Kang, Ho-Jun; Lee, Min-Seok; Suh, Sang-Jun; Lee, Jeong-Ho; Kang, Dong-Gee (Journal of cerebrovascular and endovascular neurosurgery, 2018)
Dural arteriovenous fistula (D-AVF) at the foramen magnum is an extremely rare disease entity. It produces venous hypertension, and can lead to progressive cervical myelopathy thereafter. On the other hand, the venous hypertension may lead to formation of a venous varix, and it can rarely result in an abrupt onset of subarachnoid hemorrhage (SAH) when the venous varix is ruptured. The diagnosis of D-AVF at the foramen magnum as a cause of SAH may be difficult due to its low incidence. Furthermore, when the D-AVF is fed solely by the ascending pharyngeal artery (APA), it may be missed if the external carotid angiography is not performed. The outcome could be fatal if the fistula is unrecognized. Herein, we report on a rare case of SAH caused by ruptured venous varix due to D-AVF at the foramen magnum fed solely by the APA. A review of relevant literatures is provided, and the treatment modalities and outcomes are also discussed.